Resistance on Stage: A Performative Reading of the 2021 Social Uprising in Cali - Velasco Arboleda, Jhon Jaime (2026)
This article develops a performative interpretation of the 2021 social uprising in Cali, Colombia, drawing on Jeffrey Alexander’s cultural pragmatics. The study examines the mobilization as a political-cultural performance in which multiple actors—youth groups, neighborhood organizations, artistic collectives, and Indigenous communities—constructed symbolic scripts, public dramatizations, and expressive repertoires that challenged state narratives on order, legality, and the legitimacy of protest. Using a qualitative and interpretive approach, the analysis integrates documentary sources, digital records, urban scenes, and testimonies from participants to explore the core components of social performance: scripts, actors, audiences, mise-en-scène, and power relations. Findings show that the social uprising in Cali brought together rituals, aesthetics of care, community performances, and embodied actions that reshaped the urban experience of conflict and generated a moral counter-narrative grounded in dignity, solidarity, and justice. The article concludes that the social uprising functioned as a collective dramatization that expanded forms of political participation and opened new horizons of meaning in public life.